Nisekoi : False love. Vol. 13, Don't worry - Komi, Naoshi, 1986- (Shonen Jump manga., 2016)
"It's hate at first sight when Raku Ichijo first meets Chitoge Kirisaki. Much to their chagrin, the two are forced into a false love relationship to keep the peace between their feuding gangster families. Haru has always loathed Raku because she thinks he's a no-good player, but things take a surprising turn when she finds out that Raku and Chitoge's relationship is fake and she ends up spending time with him at a festival... Meanwhile, Ruri's great-grandfather is near death, and his one request is to meet Ruri's boyfriend. Somehow, Raku gets roped into playing the part!"--Back cover.